Tell me what you want : a therapist and her clients explore our 12 deepest desires - Weber, Charlotte Fox (Atria Books, 2023)
"This inspiring and moving exploration of the twelve fundamental psychological needs we all share goes behind the closed doors of therapy to guide us in navigating our deepest longings"--